Cash's part-time job became 46-yr career - Mullings, David (Raton Range Raton, New Mexico, 1988)
Newspaper Article on Lina Cash and her career with International Bank of Raton, New Mexico.
Master list item #:49
File location is in the Raton File Cabinet
Keywords: Cash, Lina; DiLisio, Joe Sr; Bradley, Mel; Cash, Don; International State Bank; Raton High School; Local History; Biography; Life and Customs; Career; Bank; Retired; Raton, New Mexico